Psychometric Properties of the Social Defeat Scale in the Colombian Population (2024)
Theoretical Framework: Social defeat is the feeling of breaking a status or goals, due to loss or difficulty in reaching resources, humiliation or social attack, self-criticism, unfavorable social comparison and unrealistic expectations, related to psychopathology and suicidality. Objective and Method: The aim of the study was to evaluate the psychometric properties of the Social Defeat Scale in 412 Colombian adults. To explore the discriminant validity, the Social Well-being Scale was used, and to explore the convergent validity, the Okasha Suicidality Scale was used. Results and Discussion: The exploratory factor analysis showed a two-dimensional structure, both factors presented good internal consistency. Confirmatory factor analysis found good fit indicators for the unifactorial model. Convergent validity was found with suicidality and discriminant validity with social welfare. The Colombian version of the Social Defeat Scale is valid for evaluating social defeat, a relevant concept in Colombia given the high rates of social disadvantage and mental health problems in its population. Implications: Having an instrument that evaluates social defeat adapted to the Colombian context contributes to detecting mediating variables between the complex social scenario of the country and mental health, to the development of preventive and intervention strategies based on evidence, considering psychosocial aspects poorly integrated into current public health policies. Originality/Value: Currently, the scale only exists in an English version, in Brazilian Portuguese and in Spanish, validated in the Chilean population.